Comparative Modeling of a Promising Design of Engine Air Supply and Exhaust Systems with Ejection Dust Removal - Ilya A. Trusevich; Sergey V. Abdulov; Igor A. Taratorkin; Viktor B. Derzhansky (Механика машин, механизмов и материалов)
As part of the study, a literature analysis is performed on various options for increasing the efficiency of engine air supply and exhaust systems. Particular attention is paid to the use of software products for determining the resistance of the engine air supply and exhaust systems, methods and approaches to reducing it and using exhaust gases to clean the dust collector. The paper provides generalized requirements for air cleaning systems for diesel engines, according to the industry standard, and for air supply and exhaust systems for the diesel engine considered in this paper, according to technical specifications. In accordance with the objectives of the study, a description of the experiment to determine the resistance of the air cleaner without cassettes and with cassettes is presented, the models and methods used for simulation calculations that ensure the convergence of the numerical solution and implemented in the multifunctional software product for multiphysical modeling STAR-CCM+ are listed, the initial data, boundary and initial conditions are given, the verification of the developed models is performed, which established the discrepancy between the experimental indicators and the calculated results of < 5 %, a comparative analysis of the engine air supply system and the exhaust system of the basic and advanced designs is carried out. The obtained scientific and technical results confirm the possibility of implementing ejection dust extraction from the air cleaner dust collector with a dust extraction coefficient of 17 % (should be at least 12 %) in the maximum power mode, which will require a separate study, and determine the main directions of further work. For the basic design, the priority is to refine the engine air supply system in order to reduce the resistance, which significantly exceeds the required value. Installing cyclone nozzles at optimal angles relative to the flow to ensure uniform distribution of mass flow appears to be the most promising solution.